ANALYSIS OF HEAT DISTRIBUTION ON VENTILATION NETWORK IN RAMP DOWN 450 KUBANG CICAU MINE UBPE ANTAM PONGKOR - YULIANTI (NIM : 22115016), RIRIN
One of the mine sites in UBPE Antam Pongkor is ramp down 450 mines Kubang Cicau, complained by workers with the atmosphere of a hot working environment. The result of identification of the heat source located at that location consists of a permanent and non-permanent heat source. Permanent heat sources include autocompression and illumination. While non-permanent heat sources include electrical equipment, diesel equipment, explosives, human metabolism, and fan compressibility. The percentage of heat generated from autocompression is 10% in 24 hours duration, 1% light in 24 hours duration, 37 kW 19% auxiliary fan 19% in 18 hours duration, 75 kW 5% booster fan in 18 hours duration, 16% LHD in duration 9 hours, 10% wheel loader in duration of 9 hours, 21% light vehicle in duration of 3 hours, blasting heat with 1% blasting smoke in 2 hours duration, blasting heat trapped in rocks by% in 24 hours duration, human metabolism 6% in 18 hours duration and 10% fan compressibility within 18 hours. Increased heat at the study site was due to the occurrence of air recirculation in the ventilation tissue. Air temperature will increase when the heat source is not permanently operating. The increase in temperature is ± 2 ° C (32.6 ° C to 34.5 ° C) in just 1.5 hours. The air temperature will come back down when the nonpermanent heat source stops operating. The rate of decline is only about 0.1 ° C / hour. The length of the rate of decline caused the heat to be trapped long enough so that the temperature was difficult to decrease to achieve the permissible working environment condition of 30oC (Regulation of the Minister of Health of the Republic of Indonesia No. 70 of 2016). An effective heat control strategy is applied at the research site by elimination and technique control. The heat control with elimination will incur lower cost which is only the initial investment cost but the work productivity only reaches 2 - 4 hours/shift while the technique control will cost higher but will create work productivity optimally 4 - 6 hours/shift. However, for current development conditions better heat control is accomplished by elimination.